Secondary dysmyelopoiesis in patients with myelodysplastic syndromes: A review of literature and the authors' data - V N Dvirnyk; A V Kokhno; E N Parovichnikova (Терапевтический архив, 2014)
To interpret hematopoietic cell myelodysplastic changes found during the primary diagnosis of myelodysplastic syndromes or other diseases and during therapy is an enormously complex clinical and laboratory problem. In what cases do these changes serve as a manifestation of clonal disease and in what cases are these changes a result of various effects? Alimentary, toxic factors, infectious agents, and iatrogenic effects may cause myelodysplastic signs in the hematopoietic cells. This review depicts diverse hematopoietic cell dysplastic changes that can be observed as a result of the effects of one drug or another, toxic factors, and infectious agents.